An empirical examination on the links of cross-functional integration of productionmarketing, BTO competitiveness and performance - Chen, Zhixiang (2022)
Purpose – This paper is to explore how cross-functional integration (CFI) of production-marketing can impact the firm’s build-to-order (BTO) competitiveness, marketing performance (MP) and financial performance (FP). Design/methodology/approach – Empirical study with the structural equation modeling approach is applied. Six hypotheses are constructed and tested based on survey data collected from Chinese manufacturing firms. Findings – The survey data supports that production-marketing integration (PMI) improves BTO competitiveness (BTOC) and MP and that BTOC also positively affects marketing outcome which, in turn, impacts a firm’s FP. The results reveal that CFI of production-marketing is an effective approach for achieving the BTO manufacturing strategy and can improve organizational performance. Originality/value – The paper uncovers the role of CFI of production-marketing in BTO manufacturing strategy and its impacts on a firm’s MP and FP and provides important managerial implications for practitioners to improve organizational time-based competitiveness and performance in today’s time-based competition era.